Myocardial Ischaemia Due to Ruptured Left Sinus of Valsalva A Case Report - Siraj, Masoom; Hasan, Md Sharif (University Heart Journal, 2012)
Here we present a case involving a middle aged male patient suffering from ruptured left Sinus Of Valsalva (SOV) and attendant complications. The rarity of the condition presents a clinical dilemma in the diagnosis and treatment of the same. Occurrences are so rare that not much comprehensive guideline is available for the medical team to proceed with treatment. We describe how we arrived at the diagnosis by correlating the various investigations done and also the surgical correction done resulting in a satisfactory outcome. DOI: http://dx.doi.org/10.3329/uhj.v7i2.10850 University Heart. Journal Vol. 7, No. 2, July 2011